Post-hospital medical respite care for homeless people in Denmark: a randomized controlled trial and cost-utility analysis - Camilla Bring; Marie Kruse; Mikkel Z. Ankarfeldt; Nina Brünés; Maja Pedersen; Janne Petersen; Ove Andersen (BMC, 2020)
Abstract Background Being homeless entails higher mortality, morbidity, and prevalence of psychiatric diseases. This leads to more frequent and expensive use of health care services. Medical respite care enables an opportunity to recuperate after a hospitalization and has shown a positive effect on readmissions, but little is known about the cost-effectiveness of medical respite care for homeless people discharged from acute hospitalization. Therefore, the aim of the present study was to investigate the cost-effectiveness of a 2-week stay in post-hospital medical respite care. Methods A randomized controlled trial and cost-utility analysis, from a societal perspective, was conducted between April 2014 and March 2016. Homeless people aged > 18 years with an acute admission were included from 10 different hospitals in the Capital Region of Denmark. The intervention group (n = 53) was offered a 2-week medical respite care stay at a Red Cross facility and the control group (n = 43) was discharged without any extra help (usual care), but with the opportunity to seek help in shelters and from street nurses and doctors in the municipalities. The primary outcome was the difference in health care costs 3 months following inclusion in the study. Secondary outcomes were change in health-related quality of life and health care costs 6 months following inclusion in the study. Data were collected through Danish registries, financial management systems in the municipalities and at the Red Cross, and by using the EQ-5D questionnaire. Results After 3 and 6 months, the intervention group had €4761 (p = 0.10) and €8515 (p = 0.04) lower costs than the control group, respectively. Crude costs at 3 months were €8448 and €13,553 for the intervention and control group respectively. The higher costs in the control group were mainly related to acute admissions. Both groups had minor quality-adjusted life year gains. Conclusions This is the first randomized controlled trial to investigate the cost-effectiveness of a 2-week medical respite care stay for homeless people after hospitalization. The study showed that the intervention is cost-effective. Furthermore, this study illustrates that it is possible to perform research with satisfying follow-up with a target group that is hard to reach. Trial registration ClinicalTrials.gov Identifier: NCT02649595 .